Transformational Leadership of Islamic Boarding School Leaders Into Modern Islamic context in diverse Discursive - Aishah, Aishah; Nurdin, Diding (EARR (Educational Administration Research and Review), 2022)
Leadership in an islamic educational school is one of the issue that keep moving towards modern concept. Thus, this study try to potrait the phenomena and to find the background and purpose of the transformation. The study conducted through library research in which the writer to collect various source and data and the data showed that the transformation occured within the islamic borading school is to adjust with the development of the era dan global. Therefor, to be exist and contribute the the islamic development, the transformatioan is viewed as one of steps taken by scholar. Key Words: Boarding school, Leadership, Transformational